2020
DOI: 10.3390/agronomy10111818
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phosphorus Fractions and Its Availability Status in Relation to Long Term P Fertilization in Loess Plateau of China

Abstract: Excessive phosphorus (P) application can alter soil P availability and limit plant growth by compacting soil and fixation of P into different organic and inorganic forms. However, it remains uncertain whether these changes happen after limited fertilization or an excessive rate applied under the winter wheat cropping system. The current study aimed to identify the transformation of P into different organic (Po) and inorganic (Pi) fractions, and their role in the plant P uptake and winter wheat (Triticum aestiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 59 publications
5
7
0
2
Order By: Relevance
“…Finally, increasing the degree of soil aggregation could sharply reduce the loss of P through leaching, thereby promoting Po lability and mineralization (Garland et al, 2018). The results of the current study support previous claims that accumulation of labile Po as part of soil organic matter (SOM) because of the Pi fertilizer addition from the medium to long‐term field trial (12–37 years) with varying P input (Mahmood et al, 2020; McLaren et al, 2015, 2020) or the P distribution within aggregate size classes (Deng et al, 2021; He et al, 2019), highlighting that Po in the NaHCO 3 pools is an important sink of fertilizer P over the medium to long‐term. It is worth noting that Po extracted with NaHCO 3 in soil aggregates was significantly and positively correlated with physiochemical properties such as SOC, indicating that SOC was the most important determinant of labile Po change in soil aggregates (Figure 4a).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, increasing the degree of soil aggregation could sharply reduce the loss of P through leaching, thereby promoting Po lability and mineralization (Garland et al, 2018). The results of the current study support previous claims that accumulation of labile Po as part of soil organic matter (SOM) because of the Pi fertilizer addition from the medium to long‐term field trial (12–37 years) with varying P input (Mahmood et al, 2020; McLaren et al, 2015, 2020) or the P distribution within aggregate size classes (Deng et al, 2021; He et al, 2019), highlighting that Po in the NaHCO 3 pools is an important sink of fertilizer P over the medium to long‐term. It is worth noting that Po extracted with NaHCO 3 in soil aggregates was significantly and positively correlated with physiochemical properties such as SOC, indicating that SOC was the most important determinant of labile Po change in soil aggregates (Figure 4a).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding was similar to the results observed by Jalali and Ranjbar (2010), who found that P was mainly bounded to Ca compounds (HCl-P, 63.7%) in some calcareous soil. It might be because the nonlabile P is considered an indication of the soluble forms in calcareous soil and was shown to accumulate because of the transformation from other fractions after long-term mineral P combined with organic manure (Figure 2c), which improved soil Po availability and fixed as a stable P over time (Aulakh et al, 2003;Jalali & Ranjbar, 2010;Khan et al, 2021;Mahmood et al, 2020). Several other reports have also provided data on nonlabile Po after adding long-term organic amendments (Dou et al, 2000;He et al, 2004He et al, , 2006Leinweber et al, 1997), who reported that organic manure contains high levels of P and Ca, that greatly facilitate the soil Ca-associated P formation, which is thought to transform crystalline Ca-P species into relatively soluble Ca-P species.…”
Section: Effect Of Long-term P Fertilization Regimes On the Po Forms ...mentioning
confidence: 99%
“…The increments in grain yield with increasing levels of PG was due to high P content in the PG-treated soil. The grain yield was decreased at every PG rate in the second cropping season due to decreasing soil available P. Additonally, strong positive linear relationships were observed between grain yield, P uptake, and soil available P. These results are in line with previous ndings (Saha et al 2014;Mahmood et al 2020). The relationships were relatively stronger under banded compared to broadcasted plots in the rst cropping season which might be due to increased concentration of available P in soil solutions in the banded plots.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding biomass and P partitioning, the best improvements were recorded under either 120 kg P 2 O 5 ha −1 treatment or 150 kg P 2 O 5 ha −1 , and effects of these two treatments were comparable. Moreover, a balanced P fertilizer supply can improve plant growth and yield due to increased soil P availability, but excessive P input was reported to cause soil pollution and P fixation [44]. Therefore, to avoid over application of P fertilizer, the rate of 120 kg P 2 O 5 ha −1 is more appropriate.…”
Section: Discussionmentioning
confidence: 99%